Contributions of a global network of tree diversity experiments to sustainable forest plantations - Kris Verheyen; Margot Vanhellemont; Harald Auge; Lander Baeten; Christopher Baraloto; Nadia Barsoum; Simon Bilodeau-Gauthier; Helge Bruelheide; Bastien Castagneyrol; Douglas Godbold; Josephine Haase; Andy Hector; et al. (Ambio, 2016)
The area of forest plantations is increasing worldwide helping to meet timber demand and protect natural forests. However, with global change, monospecific plantations are increasingly vulnerable to abiotic and biotic disturbances. As an adaption measure we need to move to plantations that are more diverse in genotypes, species, and structure, with a design underpinned by science. TreeDivNet, a global network of tree diversity experiments, responds to this need by assessing the advantages and disadvantages of mixed species plantations. The network currently consists of 18 experiments, distributed over 36 sites and five ecoregions. With plantations 1–15 years old, TreeDivNet can already provide relevant data for forest policy and management. In this paper, we highlight some early results on the carbon sequestration and pest resistance potential of more diverse plantations. Finally, suggestions are made for new, innovative experiments in understudied regions to complement the existing network.